First serological and molecular investigation of hepatitis E virus infection in dromedary camels in Algeria - Agabou, Amir; Benaissa, Mohamed Hocine; Bouasla, Ilyes; De Sabato, Luca; Hireche, Sana; Ianiro, Giovanni; Monini, Marina; Di Bartolo, Ilaria (Frontiers in Veterinary Science, 2023)
Hepatitis E is an acute self-limited or fulminant infection in humans, caused by the hepatitis E virus (HEV). This member of the Hepeviridae family has been identified in a wide range of domestic and wild animals all over the world, with a possible transmission to humans through fecal oral route, direct contact and ingestion of contaminated meat products, making it one of the global zoonotic and public health major concerns. Since there is no monitoring program and a lack of data on HEV in animals in Algeria, the current preliminary survey has been undertaken to elucidate the exposure to the virus in camels at abattoirs of six southern provinces of Algeria. Two-hundred and eight sera/plasma were collected and analyzed (by double antigen sandwich ELISA) for the presence of total anti-HEV antibodies, among which 35.1% were positive, but no HEV RNA could be isolated from them (by two pan-HEV nested RT-PCR and broad range real-time reverse transcription RT-PCR). The univariate analysis showed significant associations (p < 0.05) between HEV seroprevalence and province of origin, age, and sex of camels, whereas the multivariable logistic regression analysis revealed a negative impact of camels’ age on it. The obtained results confirm that HEV infection is widespread established in the camelid population of Algeria.